All-fiber cylindrical vector beams laser based on the principle of mode superposition. (July 2021) - Dong, Zhipeng; Zhang, Yimin; Li, Hongxun; Tao, Runxia; Gu, Chun; Yao, Peijun; Zhan, Qiwen; Xu, Lixin
Highlights: A cylindrical vector beams laser in an all-polarization-maintaining fiber configuration. The laser with TM01 mode can maintained under certain perturbation conditions. It can be extended to generate azimuthally polarized or higher order cylinder vector modes. Abstract: We propose a novel method for the generation of a cylindrical vector beams (CVBs) laser in an all-polarization-maintaining fiber (PMF) configuration based on the principle of mode superposition. By using this method, a stable and high purity radially polarized (TM01 ) mode is obtained by stretching fiber to adjust phase shift. The laser with TM01 mode has a maximum power of (19.2 ± 0.1) mW and a slope efficiency of (22.02 ± 0.06) %, whose mode purity is approximately (91.8 ± 0.1) %. This method can be extended to generate azimuthally polarized (TE01 ) or higher order cylinder vector modes. Owing to its compact and high stability, this laser is promising for industrial processing and biomedical applications.